Case Report: Impact of Botulinum Toxin Injection on Function of Affected Upper Extremity in A Patient, 16 Years after Stroke - Malek Amini; Arian Shamili; hassan A'shayeri; Rouzbeh Kazemi (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: Case report Impact of Botulinum Toxin injection on function of affected upper extremity in a patient after 16 years since stroke (CVA). Botulinum toxin injection is one the treatments in spasticity reduction and consequently in recovery of upper limb function in stroke patients. The purpose of this case study is to report the effect of Botulinum toxin injection on upper extremity function after 16 years of stroke. Materials & Methods: The patient was a 63-year-old man who has had a cerebrovascular accident that happened in the left hemisphere about 16 years ago, and as a result, a paresis in dominant hand and arm. Although the patient was able to perform simple movements but he was complaining about the slowness and stiffness in the movements. To treat spasticity the Botulinum toxin type A was used. Injection into selected muscles of hemiparetic upper limb was done by a specialist physician and was between 50-150IU based on specific volume of each muscle. After injection, the patient was monitored for 3 months and at the end of each month, the assessments were reevaluated. During this period, although research team suggested the patient to continue the rehabilitation but for personal reasons he didn't participate in any treatment and didn`t receive any other antispasmodic medications. Results: An increase in range of motion was seen in all joints but this improvement was not significant. The greatest improvement in passive and active range of motion was seen in Metacarpophalengeal joints. At the end of each month, compared to the first month the recovery of function in upper extremity was significant. Maximum recovery of upper extremity function was related to the hand section of fugl-meyer assessment. At the end of the first month, spasticity significantly decreased so that the patient was able to extend all his joints more easily than before injection. Although spasticity never reached zero. Conclusion: Botulinum toxin injection even after 16 years of stroke may improve the function of upper extremity.